GLUT1 reductions exacerbate Alzheimer's disease vasculo-neuronal dysfunction and degeneration - Winkler, Ethan A; Nishida, Yoichiro; Sagare, Abhay P; Rege, Sanket V; Bell, Robert D; Perlmutter, David; Sengillo, Jesse D; Hillman, Sara; Kong, Pan; Nelson, Amy R; Sullivan, John S; Zhao, Zhen; et al. (Nature neuroscience, 2015)
Winkler et al . show that the glucose transporter GLUT1 in brain endothelium is necessary for the maintenance of proper brain capillary networks and blood-brain barrier integrity. The study also shows that loss of GLUT1 in a mouse model of Alzheimer's disease accelerates BBB breakdown, perfusion and metabolic stress resulting in behavioral deficits, elevated amyloid beta levels and neurodegeneration. The glucose transporter GLUT1 at the blood-brain barrier (BBB) mediates glucose transport into the brain. Alzheimer's disease is characterized by early reductions in glucose transport associated with diminished GLUT1 expression at the BBB. Whether GLUT1 reduction influences disease pathogenesis remains, however, elusive. Here we show that GLUT1 deficiency in mice overexpressing amyloid β-peptide (Aβ) precursor protein leads to early cerebral microvascular degeneration, blood flow reductions and dysregulation and BBB breakdown, and to accelerated amyloid β-peptide (Aβ) pathology, reduced Aβ clearance, diminished neuronal activity, behavioral deficits, and progressive neuronal loss and neurodegeneration that develop after initial cerebrovascular degenerative changes. We also show that GLUT1 deficiency in endothelium, but not in astrocytes, initiates the vascular phenotype as shown by BBB breakdown. Thus, reduced BBB GLUT1 expression worsens Alzheimer's disease cerebrovascular degeneration, neuropathology and cognitive function, suggesting that GLUT1 may represent a therapeutic target for Alzheimer's disease vasculo-neuronal dysfunction and degeneration.